OPTIMIZATION OF THE RECIPE COMPOSITION OF BAKERY PRODUCTS FOR SPORTS NUTRITION - Nevskaya E.V.; Shlelenko L.A.; Borodulin D.M. (Техника и технология пищевых производств)
A proper nutrient adapted diet considering the specific kind of sport, sex and individual characteristics of sportsmen is necessary for achieving high sports results. Therefore, the development of bakery products, which are nutrient adapted to the sportsmen nutrition, optimization of ingredient composition of bakery products with regard to technological properties of raw materials and biomedical recommendations will not only contribute to the achievement of better athletic results, but also prevent a number of alimentary-dependent diseases and conditions of this population category, that is a significant task. The article presents the data on the optimization of ingredient composition of bakery products with regard to technological properties of raw materials and biomedical recommendations for sportsmen nutrition. The list of ingredients with immunomodulating and antioxidant properties and their application in the production of specialized bakery products of sports nutrition have been scientifically proved. The optimization has been performed with the use of modern programs involving mathematical modeling of product recipes in the implemented range of parameter changes. Qualitative and quantitative recipe composition has been modeled in accordance with the biomedical requirements to foods for sportsmen taking into account their physical activities. The interconnection between the mass fraction of protein components (garbanzo bean flour and egg albumin) and physical and chemical quality indices of bakery products for sportsmen nutrition has been established. It has been experimentally proved that the use of the developed recipe compositions helps to increase the content of proteins, fats, carbohydrates, vitamins, minerals. It will increase the biological value and total content of water-soluble antioxidants in bakery products for the nutrition of sportsmen during their active training before competitions.